Big trouble in Little China - Twentieth Century-Fox Film Corporation; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2007)
Big trouble in Little China: DVD; full screen (1.33:1) and widescreen (2.35:1) presentation; dual layer; 4.1 Dolby digtial surround (English), stereo. (French), mono. (Spanish); NTSC region 1.; Flight of the phoenix: DVD; full screen (1.33:1) presentation; dual layer; 5.1 Dolby digital surround (English), 5.1 DTS (English), Dolby digital surround (French); NTSC region 1.
Big trouble in Little China: DVD; full screen (1.33:1) and widescreen (2.35:1) presentation; dual layer; 4.1 Dolby digtial surround (English), stereo. (French), mono. (Spanish); NTSC region 1.; Flight of the phoenix: DVD; full screen (1.33:1) presentation; dual layer; 5.1 Dolby digital surround (English), 5.1 DTS (English), Dolby digital surround (French); NTSC region 1.
Big trouble in Little China: Originally released as a motion picture in 1986. Big trouble in Little China: Special features include commentary by John Carpenter and Kurt Russell; original theatrical trailer. Flight of the phoenix: Based on a screenplay by Lukas Heller and the novel by Elleston Trevor. Flight of the phoenix: Originally released as a motion picture in 2004; remake of 1965 motion picture. Flight of the phoenix: Special features include full-length audio commentary by director John Moore, producers John Davis and Wyck Godfrey, and production designer, Patrick Lumb; featurette "The Phoenix Diaries," making-of documentary; deleted and extended scenes; over 15 minutes of never-before-seen footage.
Music, John Carpenter in association with Alan Howarth ; director of photography, Dean Cundey ; edited by Mark Warner, Steve Mirkovich, Edward A. Warschilka.
Kurt Russell, Kim Cattrall, Dennis Dun, James Hong, Victor Wong, Kate Burton, Donald Li, Carter Wong, Peter Kwong, James Pax.
MPAA rating: PG-13.
DVD, Dolby digital.
Keywords: Truck drivers -- United States -- Drama; Kidnapping -- Drama; Supernatural -- Drama; Airtraffic accidents -- Drama; Transport planes -- Drama; Chinatown (San Francisco, Calif.) -- Drama; Martial arts films; Action and adventure films; Feature films; Video recordings for the hearing impaired